THE POLITICAL COMMUNICATION STRATEGY OF PARTAI GOLONGAN KARYA IN REGIONAL HEAD ELECTION YEAR 2018 - Haris Sasilo; Sapta Sari; Indria Indria (SENGKUNI Journal (Social Science and Humanities Studies), 2020)
This study aims to determine the political communication strategy of the golongan Karya (golkar) party in regional head elections. Data retrieval techniques that researchers use are interviews, documentation, and observation. Data collection techniques by purposive sampling by taking informants as many as 3 people. This study uses a qualitative descriptive method using the positioning theory from adam nursal (andianus pito: 2013) consisting of 1) policy is an offer of work programs delivered by candidates to the pubic 2)person is a candidate who has high quality and track record 3). This party is an apolitical product that has been done by the Golkar party 4). Presentation is the presentation of work programs submitted by the golkar party to the pubic directly. The results of the research and discussion that the positioning theory carried out by the DPD golongan Karya (Golkar) party is able to take sympathy and can influence the message conveyed to the public.